Technical considerations to avoid delayed and non-union. (June 2017) - McMillan, Tristan E.; Johnstone, Alan J.
Abstract: For many years intramedullary nails have been a well accepted and successful method of diaphyseal fracture fixation. However, delayed and non unions with this technique do still occur and are associated with significant patient morbidity. The reason for this can be multi-factorial. We discuss a number of technical considerations to maximise fracture reduction, fracture stability and fracture vascularity in order to achieve bony union.